Complete mitochondrial genome of the planthopper Orthopagus splendens (Germar, 1830) (Hemiptera: Fulgoromorpha: Dictyopharidae). Issue 9 (2nd September 2021) - Zheng, Yan-li; Bourgoin, Thierry; Yang, Lin; Chen, Xiang-Sheng; Luo, Xu-Qiang; Luo, Guang-Jie
Abstract: The first complete mitochondrial genome of a dictyopharid planthopper, Orthopagus splendens (Germar, 1830) (Hemiptera: Fulgoroidea: Dictyopharidae) is sequenced. The 15, 349 bp long complete mitogenome contains 13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes, and 1 A + T-rich region with an arrangement identical to that observed in most insect mitogenomes (GenBankNo. MW441850). All PCGs start with ATN, and end with TAN or single T ( nad1, nad5, and atp6 ). A phylogenetic analysis places O. splendens as sister to Fulgoridae confirming a sister relationship between Dictyopharidae and Fulgoridae.